Non-Cyclical Mastalgia and its Effects on Daily Life among Women Visiting the Breast Disease Treatment Center at Shar Hospital in Sulaymaniyah City, Iraq - Rahim, Kwestan Mohammed; Hamasur, Heshw Othman; Rahim, Khalat Kamal; Rostam, Darya Abdulmajid (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Breast discomfort or pain, known as mastalgia, is a frequent symptom among female patients throughout their lifespan. Identification of the underlying causes through evaluation and target imaging is required for the patients' comfort. Aim: To assess the primary variables that cause non-cyclical mastalgia and how it affects women's lives. Methods: A quantitative-descriptive prospective study on a randomized, selected sample group of 100 patients with non-cyclical mastalgia in Breast Disease Treatment Center at Sulaimaniyah was done. A prepared questionnaire was used to interview the participants from January 15 to January 22, 2023. Results: Out of the 354 women who presented to the Breast Treatment Clinic during the study period, 100 (28.23%) were diagnosed with non-cyclical mastalgia. The common breast disorders among participants were simple, complex cyst and fat tissue necrosis on ultrasound. Mastalgia effects on daily life, interferes with usual sleep patterns of women (P=0.003), causes anxiety (P=0.001), had negative effect on exercise (P=0.002) and daily work (P=0.01) of women. Conclusions: Women over 40 years old who experience fear, tension, and anxiety due to the consequences of mastalgia, which interfere with regular sleep patterns and have an adverse effect on exercise and regular job duties, and most of them have breast problems on imagining, are more likely to suffer from non-cyclical mastalgia.
Keywords: Noncyclical mastalgia; Causes; lifestyle quality; Prevalence